UKALLXII/ECOG2993: addition of imatinib to a standard treatment regimen enhances long-term outcomes in Philadelphia positive acute lymphoblastic leukemia. - Fielding, A; Rowe, J; Buck, G; Foroni, L; Gerrard, G; Litzow, MR; Lazarus, H; Luger, S; Marks, D; McMillan, A; Moorman, A; Patel, B; et al. (2014)
The Philadelphia chromosome positive arm of the UKALLXII/ECOG2993 study for adult acute lymphoblastic leukemia (ALL) enrolled 266 patients between 1993 and 2003 (pre-imatinib cohort). In 2003 imatinib was introduced as a single-agent course following induction (N = 86, late imatinib). In 2005 imatinib was added to the second phase of induction (N = 89, early imatinib). The complete remission (CR) rate was 92% in the imatinib cohort vs 82% in the preimatinib cohort (P = .004). At 4 years, the overall survival (OS) of all patients in the imatinib cohort was 38% vs 22% in the preimatinib cohort (P = .003). The magnitude of the difference between the preimatinib and imatinib cohorts in event-free survival (EFS), OS, and relapse-free survival (RFS) seen in univariate analysis was even greater in the multivariate analysis. In the preimatinib cohort, 31% of those starting treatment achieved hematopoietic stem cell transplant (alloHSCT) compared with 46% in the imatinib cohort. A Cox multivariate analysis taking alloHSCT into account showed a modest additional benefit to imatinib (hazard ratio for EFS = 0.64, 95% confidence interval 0.44-0.93, P = .02), but no significant benefit for OS and RFS. Adding imatinib to standard therapy improves CR rate and long-term OS for adults with ALL. A proportion of the OS benefit derives from the fact that imatinib facilitates alloHSCT. This trial was registered at clinicaltrials.gov as NCT00002514.